2018
DOI: 10.3389/fnbot.2018.00074
|View full text |Cite
|
Sign up to set email alerts
|

A Linear Approach to Optimize an EMG-Driven Neuromusculoskeletal Model for Movement Intention Detection in Myo-Control: A Case Study on Shoulder and Elbow Joints

Abstract: The growing interest of the industry production in wearable robots for assistance and rehabilitation purposes opens the challenge for developing intuitive and natural control strategies. Myoelectric control, or myo-control, which consists in decoding the human motor intent from muscular activity and its mapping into control outputs, represents a natural way to establish an intimate human-machine connection. In this field, model based myo-control schemes (e.g., EMG-driven neuromusculoskeletal models, NMS) repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…Finally, these results are related to NNMF and might differ for other algorithms and models. Therefore, while the introduced concept may have impact for the field of muscle synergies and rehabilitation, the presented results generalize only for the forearm and hand applications and may find applications including prosthesis [55] and movement intention detection [56]. This work will be the starting point for a more detailed analysis of hand grasps based both on muscle and kinematic patterns, as done on previous pioneering work [57], where it was demonstrated that a more compact representation and a higher decoding capacity of grasping tasks is found when movements are expressed in the muscle kinematics domain rather than kinematic alone.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, these results are related to NNMF and might differ for other algorithms and models. Therefore, while the introduced concept may have impact for the field of muscle synergies and rehabilitation, the presented results generalize only for the forearm and hand applications and may find applications including prosthesis [55] and movement intention detection [56]. This work will be the starting point for a more detailed analysis of hand grasps based both on muscle and kinematic patterns, as done on previous pioneering work [57], where it was demonstrated that a more compact representation and a higher decoding capacity of grasping tasks is found when movements are expressed in the muscle kinematics domain rather than kinematic alone.…”
Section: Discussionmentioning
confidence: 99%
“…We used a Multi-Objective Genetic Algorithm (MOGA) to find the optimal network topology. A genetic algorithm is a powerful optimization technique that reflects the process of natural selection where the fittest individuals are selected for reproduction in order to produce offspring of the next generation, thus explaining its feasibility in several research domains [40, 41]. The MOGA algorithm was configured to find the optimum varying the following network parameters: (i) number of hidden layers (integer interval: 1 to 3), (ii) number of neurons per layer (integer interval: 1 to 256 for the first hidden layer and 0 to 255 for other ones), and (iii) activation functions for each layer (one among: log-sigmoid - logsig, hyperbolic tangent sigmoid -tansig, pure linear - purelin and symmetric saturating linear - satlins).…”
Section: Methodsmentioning
confidence: 99%
“…In this work, we designed and tested several CNNs architectures for the segmentation of the images. Since optimising the architecture of classifiers is still an open problem [3436], often faced with evolutionary approaches, we decided to start from a well-known general CNN, the VGG-16 [37], and modify its structure varying several parameters.…”
Section: Methodsmentioning
confidence: 99%